Peran Alumni Madrasah Aliyah Negeri 3 Agam di Masyarakat - Fitri Annisa; Muhiddinur Kamal; Endri Yenti; Januar Januar (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Researchers conducted research at Madrasah Aliyah Negeri 3 Agam which was motivated by the strategic role of madrasah alumni which has not been maximized in society. This research aims to describe the strategic role of Madrasah Aliyah Negeri 3 Agam alumni in carrying out their roles in society and to determine the role of Madrasah Aliyah in preparing alumni so they can carry out their strategic roles in society. This problem is researched using descriptive qualitative research methods which are aimed at describing and analyzing the phenomenon of events, social activities, attitudes, beliefs, thoughts of people individually and in groups using the type of case study research. To analyze the data, researchers grouped it based on existing problems. Based on the findings of research conducted by the author, the results show that: the strategic role of Madrasah Aliyah Negeri 3 Agam alumni has not been fully maximized. The role of madrasah aliyah in preparing alumni so they can carry out their strategic roles in society, including First, developing madrasah culture. Second, through extracurricular activities. Furthermore, there are three strategic roles of madrasa alumni in society, namely: alumni as filters of community religious activities, alumni as educators and contributors of progressive ideas for the benefit of development in the community area, and alumni as advocates and servants of the wider community in the eyes of the state.